Estimation of Irrigation Water Requirement for Land Preparation of Ricefield in Irrigation Modernization - Andri Andri; Murtiningrum Murtiningrum; Ngadisih Ngadisih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Irrigation water requirement for irrigation for land preparation is the highest water requirement in rice cultivation therefore it was essential to determine it based on recent condition in order to support the irrigation modernization. This research aimed to determine the irrigation requirement and tillage specific drafts based for various water ponding level in rice field as well as to determine parameters of irrigation requirement for land preparation to support irrigation modernization. Determination of irrigation water requirement is computed based on equation developed by Van de Goor and Zijlstra (1968) with variation of water volume supplied for saturation and ponding level. Variation of water supplied during land preparation resulted in the variation of tillage specific drafts according to empirical formula developed by Kisu (1972). Water level ponding of 0 mm, 5 mm, 30 mm, and 74 mm resulted in water requirements for land preparation (Project Water Requirement/PWR) of 112 mm, 122 mm, 139 mm, and 198 mm, respectively. The mentioned water ponding level resulted in the tillage specific draft of 1.131 kg/cm2, 1.101 kg/cm2, 0.886 kg/cm2, and 0.954 kg/cm2, respectively. The thicker water ponding in the rice field, the more water requirement for land preparation, but the less energy needed for tillage. Recommended irrigation requirement for land preparation was 139 mm with 15-day duration of land preparation.  Keywords: Irrigation modernization, Irrigation requirement, Land preparation, Tillage specific draft, Ponding